Predicting respiratory distress syndrome at birth using a fast test based on spectroscopy of gastric aspirates: 2. Clinical part. (31st May 2019) - Heiring, Christian; Verder, Henrik; Schousboe, Peter; Jessen, Torben E.; Bender, Lars; Ebbesen, Finn; Dahl, Marianne; Eschen, Christian; Fenger‐Grøn, Jesper; Höskuldsson, Agnar; Matthews, Morgaine; Reinholdt, Jes; et al.
Abstract: Aim: To evaluate the accuracy of our new rapid point‐of‐care (POC) test for lung maturity. The method as we describe in an accompanying article was developed with the purpose of improving the outcome from respiratory distress syndrome (RDS). The test enables the delivery of surfactant in infants with immature lungs already at birth and ensures that infants with mature lungs are not treated unnecessarily. Methods: Fresh gastric aspirate (GAS) was sampled at birth in a cohort of preterm infants with gestational ages ranging between 24 and 31 completed weeks for lung surfactant measurement as lecithin–sphingomyelin ratio (L/S). L/S was prospectively compared with RDS development. The clinical outcome was blinded for the investigators of L/S. The time for analysis was <15 minutes. Results: GAS was obtained from 72 infants. Forty‐four (61%) developed RDS. The cut‐off for L/S was 3.05; predicting RDS with a sensitivity of 91% and specificity of 79%. Conclusion: The new improved spectroscopic L/S method of lung maturity on GAS has high sensitivity. The method is designed for use as a POC test at birth, and a spectroscopic prototype has been developed for bedside use. Clinical trials with this new lung maturity test are planned.